If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6g + 7g + -7 = 0 Reorder the terms: -7 + -6g + 7g = 0 Combine like terms: -6g + 7g = 1g -7 + 1g = 0 Solving -7 + 1g = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 1g = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 1g = 0 + 7 1g = 0 + 7 Combine like terms: 0 + 7 = 7 1g = 7 Divide each side by '1'. g = 7 Simplifying g = 7
| b^2+12=0 | | 4x+4k=2x+14k | | 24/24 | | 10x+28=3x+147 | | 7.5=1.5a | | -2z+10=-4+5z | | -2x+10=#4+5x | | 34=r/3.2 | | -7y=39 | | 100/1.5 | | 53x-2x=9x+20 | | x^3-3x^2-54=0 | | 2x-16=47 | | -5r^2+25r^3+10r^2=0 | | -27-5x=8-19x | | 7+4v=13 | | 8j+6=214 | | 3x+6=24-3x | | 12=3M-1.5 | | 45*98= | | 3G-9=36 | | 3/4(2x+3)-31/2=4/5(1-x) | | 24=6+3a | | 37=8f+7 | | 3y-5=0.5(5y+1) | | 5-3y=17-7y | | 7y=50-3y | | f(x)=3x^2-7x-11 | | 5x+2x+6=9x+2 | | 2x+16=3x+7 | | -x+6(-4)=1 | | 4x+8=6x+2 |